1-(2,4-Dinitrophenyl)-2-[(E)-(3,4,5-trimethoxybenzylidene)]hydrazine - Suchada Chantrapromma; Pumsak Ruanwas; Nawong Boonnak; C. S. Chidan Kumar; Hoong-Kun Fun (Acta Crystallographica Section E, 2014)
Molecules of the title compound, C16H16N4O7, are not planar with a dihedral angle of 5.50 (11)° between the substituted benzene rings. The two meta-methoxy groups of the 3,4,5-trimethoxybenzene moiety lie in the plane of the attached ring [Cmethyl–O–C–C torsion angles −0.1 (4)° and −3.7 (3)°] while the para-methoxy substituent lies out of the plane [Cmethyl—O—C—C, −86.0 (3)°]. An intramolecular N—H...O hydrogen bond involving the 2-nitro substituent generates an S(6) ring motif. In the crystal structure, molecules are linked by weak C—H...O interactions into screw chains, that are arranged into a sheet parallel to the bc plane. These sheets are connected by π–π stacking interactions between the nitro and methoxy substituted aromatic rings with a centroid–centroid separation of 3.9420 (13) Å. C—H...π contacts further stabilize the two-dimensional network.